(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The offshore renewable energy sector has seen a rise in floating devices, all of which require mooring and anchoring systems. Synthetic ropes have emerged as a promising technology for cost reduction in this system. However, characterising the behaviour of these materials, which exhibit complex non-linear, visco- elastic and plastic structural properties, presents challenges. Numerical modelling and tank testing are the available tools for developers to overcome these challenges, however, there is a lack of guidelines for test facilities regarding the design of tank-scale mooring systems. The present work focuses on the numerical design of a typical semi-taut mooring system using synthetic materials suitable for future-generation floating offshore wind turbines. A coupled time-domain hydrodynamic model was employed to explore the dynamic sensitivity of the device to changes in mooring rope stiffness. The results demonstrate that changes in line axial stiffness have a greater impact on platform surge and mooring line tension than on heave and pitch responses. These findings establish preliminary margins for target stiffness values, which are valuable for selecting mooring materials for scaled tank test models. Although the case study was floating wind, the results have broader applicability to wider floating marine energy device design.